Hall effect for indirect excitons in an inhomogeneous magnetic field - Arnardottir, K. B. (2013)
We study the effect of an inhomogeneous out-of-plane magnetic field on the behavior of two-dimensional (2D) spatially indirect excitons. Due to the difference of the magnetic field acting on electrons and holes, the total Lorentz force affecting the center of mass motion of an indirect exciton appears. Consequently, an indirect exciton acquires an effective charge proportional to the gradient of the magnetic field. The appearance of the Lorentz force causes the Hall effect for neutral bosons, which can be detected by measurement of the spatially inhomogeneous blueshift of the photoluminescence using a counterflow experiment.